PENGARUH PEMBERIAN BIOURIN KAMBING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea Mays var. Saccharata Sturt) - Febriana, Anisa; Podesta, Fiana; Fitriani, Dwi; Suryadi, Suryadi (BUANA SAINS, 2024)
This study aimed to determine the effect of biourin on the growth and yield of sweet corn (Zea mays Saccharata Sturt). This research was conducted at the Bengkulu Agricultural Instrument Standards Implementation Center (BPSIP). This research was carried out using a Completely Randomized Design (CRD), with four treatments of biourin liquid organic fertilizer. P0: Control (NPK fertilizer), P1: 50 ml/l water, P2: 100 ml/l water, P3: 150 ml/l water each treatment was repeated seven times.  The results of this study showed that the provision of goat biourin had no significant effect on the parameters of plant height (14 and 28 hst), the number of leaves (14, 28, and 42 hst), stem diameter (14, 28 and 42 hst), cob length, cob length without cob, the diameter of the cob with weighed cob, the diameter of the cob without weighed cob, crown wet weight, crown dry weight, root wet weight, root dry weight and which significantly influenced the parameters of plant height (42 hst), weight of the cob with weighed cob, and weight of the cob without weighed cob.